Prevalence of HPV infection among Greek women attending a gynecological outpatient clinic - Stamataki, Petroula; Papazafiropoulou, Athanasia; Elefsiniotis, Ioannis; Giannakopoulou, Margarita; Brokalaki, Hero; Apostolopoulou, Eleni A.; Saroglou, George; Sarafis, Pavlos (My University, 2010)
Background: Human papillomavirus (HPV) infection is a causative factor for cervical cancer. Early detection of high risk HPV types might help to identify women at high risk of cervical cancer. The aim of the present study was to examine the HPV prevalence and distribution in cervical smears in a sample of Greek women attending a gynecological outpatient clinic and to explore the determinants of the infection.Methods: A total of 225 women were studied. All women underwent a regular gynecological control. 35 HPV types were studied; 6, 11, 16, 18, 26, 31, 33, 35, 39, 40, 42, 43, 44, 45, 51, 52, 53, 54, 56, 58, 59, 61, 62, 66, 68, 70, 71, 72, 73, 81, 82, 83, 84, 85 and 89. Also, basic demographic information, sociodemographic characteristics and sexual behavior were recorded.Results: HPV was detected in 22.7% of the study population. The percentage of the newly diagnosed women with HPV infection was 17.3%. HPV-16 was the most common type detected (5.3%) followed by HPV-53 (4.9%). 66.2% of the study participants had a Pap test during the last year without any abnormalities. HPV infection was related positively with alcohol consumption (OR: 2.19, 95% CI: 1.04-4.63, P = 0.04) and number of sexual partners (OR: 2.16, 95% CI: 1.44-3.25, P < 0.001), and negatively with age (OR: 0.93, 95% CI: 0.87-0.99, P = 0.03), and monthly income (OR: 0.63, 95% CI: 0.44-0.89, P = 0.01).Conclusion: The prevalence of HPV in women attending an outpatient clinic is high. Number of sexual partners and alcohol consumption were the most significant risk factors for HPV infection, followed by young age and lower income.
Keywords: Uterine Cervical Neoplasms; Papillomavirus Infections; Genotype distribution